Avaliação da infraestrutura cicloviária implantada em 2021 e 2022 em Belém-PA - ALFAIA, Bruno Moraes de (2023)
Due to the importance of Cycling Infrastructure for cities, there have been great advances in the National Urban Mobility Policy, giving priority to non-motorized transport over motorized. However, although in the Metropolitan Region of Belém there were implementations of bicycle lanes between the years 2021 and 2022, it is not enough to simply create new bicycle structures, it is necessary to ensure that they meet the various technical and legal aspects, in order to meet the daily needs of the population. the day-to-day life of cities. Therefore, the objective of the work is to analyze eleven cycle lanes implemented in Belém-PA, in the years 2021 and 2022, regarding the geometric design, paving and signaling, identify the critical points and propose solutions to mitigate them. In this way, research was carried out in loco, through surveys of data from the implemented cycle lanes, such as the width of the carriageways and cycle lanes, separating elements between the lanes, types of signaling, main problems and critical points found in each section of the lanes. bike lanes. The main results found were: In an analysis of 13.6 km of cycle lanes, 112 problems were found. Of the 11 cycle lanes studied, 10 had geometric design irregularities, 9 exhibited asphalt paving irregularities and 8 cycle lanes had signaling irregularities. The bike lane that comes closest to the standards of the 2001 Cycle Planning Manual (GEIPOT) is Portal da Amazon and the bike lane that presents the most nonconformities is Avenue 16 de November in Mosqueiro. Finally, it was found that although the cycling network has increased, there are still several problems to be solved.